Implementation of Smart Meeting Room Videowall All in One Using Project Management Framework Methodology at PT. Pupuk Sriwidjaja Palembang - Azhari, Muhammad; Febrian, Muhammad; Sutabri, Tata (Brilliance: Research of Artificial Intelligence, 2023)
Smart meeting room is a "smart" meeting room that integrates hardware and software in one meeting room. The design of a smart meeting room videotwall all in one at PT Pupuk Sriwidjaja Palembang is expected to facilitate communication, discussion and negotiation based on meetings, for which an audio-visual system is needed in each conference room. Starting with the pandemic that occurred in Indonesia in early 2020, some companies implemented remote work that did not require employees to come to the office, employees now work remotely more often. Therefore, advances in audio-visual technology and video conferencing are a growing trend that shows no signs of slowing down. This design system aims to create a productive meeting experience for employees of PT Pupuk Sriwidjaja Palembang, whether the participants join directly from the office or remotely. The design of all in onebased meeting room at PT Pupuk Sriwidjaja Palembang using project management framework. The results of this research can facilitate interaction and communication during meetings, smart meeting rooms are equipped with audio and visual support technology. One form of realization of IoT technology in smart meeting room components is its ability to enable automatic settings, both in temperature settings and light settings that can be controlled easily and integrated from just one intuitive touch panel. Therefore, with the design of a smart meeting room based on all in one at PT Pupuk Sriwidjaja Palembang using togaf framework will facilitate the booking system automatically, because all smart meeting room booking processes will be automated easily and quickly. The smart meeting room is actually equipped with various supporting all components, such as a wireless smart screen, which can also function as a smart whiteboard, a set of video conference tools equipped with a microphone to facilitate communication, and a platform with integrated controls to manage all devices.